IMPROVING STUDENTS’ WRITING ACHIEVEMENT IN ANALYTICAL EXPOSITION TEXT THROUGH GUIDED WRITING TECHNIQUE AT THE ELEVENTH GRADE STUDENTS OF MAN KRECEK PARE KEDIRI - handhita, rahma eka (LENTERA : Jurnal Pendidikan dan Pengajaran, 2018)
This is a classroom action research which aimed to describe the using of Guided Writing Technique improve the students’ writing achievement in analytical exposition text at the eleventh grade students of MAN Krecek Pare Kediri and the result of students’ writing achievement in analytical exposition text through Guided Writing Technique. The setting of the research is the eleventh grade students of science program 3 at MAN Krecek Pare Kediri. There were 37 students in which were consisted of 9 male students and 28 female students. The instruments of the study were interview, observational form, questionnaire and writing test. Based on the result of the preliminary test which, it showed that the subjects’ writing analytical exposition text was categorized as insufficient, which was 67.24. The present classroom action research then was carried out by implementing guided writing technique in two-planned cycles. From the technique implemented, there was significant improvement from the subjects’ writing analytical exposition text, in which it improved from insufficient to good, which was 72.89 in cycle I and 81.02 in cycle II. Furthermore, the research could bring the improvement to the subjects’ writing analytical exposition text by implementing the technique. To sum up, the present classroom action study proved that guided writing technique could improve the writing achievement of the eleventh grade students of MIA 3 at MAN Krecek Pare Kediri. In addition, the factors that influence the improvement of students’ achievement in writing were teacher’s factor (classroom management and teacher’s explanation) and students’ factor (students’ attention, participation and interest).